High‐Pressure Synthesis and Crystal Structure of the Highly Condensed Yttrium Borate YB7O12. Issue 2 (8th January 2019) - Fuchs, Birgit; Schmitt, Martin K.; Wurst, Klaus; Huppertz, Hubert
Abstract : The yttrium borate YB7 O12 was obtained in a high‐pressure/high‐temperature experiment at 10 GPa and 1573 K. The crystal structure was clarified by X‐ray single‐crystal diffraction, where the compound was found to crystallize in the orthorhombic space group Pccn (no. 56) with the lattice parameters a = 11.985(2), b = 6.717(6), c = 7.867(7) Å, and a volume of V = 633.0(1) Å 3 . Built up exclusively from BO4 tetrahedra, YB7 O12 features an exceptionally high degree of condensation, which originates from the finding that every tetrahedron contains two threefold‐coordinated oxygen atoms. The compound was further characterized by X‐ray powder diffraction. Abstract : YB7 O12 was synthesized by a high‐pressure/high‐temperature reaction at 10 GPa and 1573 K. It crystallizes in the orthorhombic space group Pccn (no. 56) with a = 11.9846(11), b = 6.7168(6), and c = 7.8636(7) Å. The compound is built up exclusively from BO4 tetrahedra including threefold coordinated oxygen atoms exhibiting a highly condensed tetrahedral network.